Theoretical and experimental research on the punching shear capacity of reinforced concrete column footings rested on the ground. (15th December 2021) - Bonić, Zoran; Zlatanović, Elefterija; Brčić, Stanko; Blagojević, Predrag; Romić, Nikola; Cvetković, Dušan
Highlights: Punching behaviour of RC column footings rested on the ground is studied. A new analytical model for the punching shear capacity assessment is proposed. Experimental tests on footing punching failure are conducted in in situ conditions. The proposed model is evaluated by comparison with the existing design codes. The proposed model has a significantly better agreement with the experimental results. Abstract: The assessment of the punching shear capacity of column footings in the current design codes is proposed mainly on the basis of experiments performed on slabs. Experimental investigations considering reinforced concrete foundations were rather rare and they were mostly performed in laboratory conditions, whereby the soil was simulated in various ways, most often with springs, hydraulic jacks, and line supports, whereas only a small part of experimentally investigated foundations was tested on the ground. Precisely for that reason, this study is aimed to determining the punching shear capacity of column footings in more realistic terms regarding the footing resting. For this purpose, the given problem is considered from two aspects – analytical and experimental. Firstly, a novel analytical approach to assessment of the punching shear capacity of column footings without shear reinforcement has been proposed, referring to the theory of reinforced concrete, by taking into consideration all relevant factors related to concrete, tensile reinforcement, as well as subsoil reactive pressures, both for the case of concentrically loaded footings and for the case of eccentrically loaded footings. Furthermore, an experimental investigation of footing punching has been conducted in in situ conditions, wherein the foundations were laid on a subgrade cohesionless soil with the predesigned and controlled properties. Lastly, the results obtained on the basis of the proposed analytical procedure and conducted experimental tests, both the own ones and of other authors, have been compared with the results according to the European (Eurocode 2), American (ACI 318-19), and fib Model Code 2010 standards. The research results have revealed that the proposed analytical approach, which comprehensively considers the relevant parameters, gives values of the punching shear capacity of reinforced concrete column footings that are closer to the experimentally obtained values when compared to the values obtained according to the considered design regulations.